Pengaruh Jumlah Daun yang disisakan pada Pemangkasan Cabang Lateral terhadap Hasil Polong Muda Tanaman Kacang Panjang (Vigna sinensis L.) - KETUT SRINING; I GUSTI NGURAH RAKA; A.A. MADE ASTININGSIH; I KETUT ARSA WIJAYA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2019)
The Effect of Lateral Branch Trimming Against Results and Quality of LongBean Seeds (Vigna sinensis L.) This study aims to determine the effect of the number of leaves that are left on the lateral branch roasting on the results of young pods of long bean plants. Thistudy uses a randomized block design (RBD). Treatment of the number of leaves lefton lateral branch pruning includes: total lateral pruning, leaving 2 leaves, leaving 4eaves, leaving 6 leaves and leaving 8 leaves on lateral branch pruning. This researchwas repeated 5 times, so as many as 25 experimental units were obtained. Variablesobserved included: main stem length, total number of leaves per plant, total leaf areaper plant, fresh weight and oven dry weight of plant parts above ground, number ofharvest pods per plant, fresh pod weight per plant, weight of oven dried pods perplant and the weight of fresh pods per hectare. The results showed that more leaveswere left on the lateral branch pruning causing the number of leaves, leaf area,weight of the plant part above the ground, and oven dry weight of the plant part onhe ground to increase. Total lateral pruning pruning treatment resulted in the numberof crop harvest pods, fresh pod weight, and oven pod dry weight with the highestaverage value. The total lateral pruning treatment resulted in the highest per hectarefresh pod weight of 25.59 tons.